The effect of relationship marketing on company performance: a case study of the sawmill industry in Terengganu / Ahmad Bazli Razali, Mohd Azizuddin Abdullah and Wan Nurulain Nabilah Wan Ibrahim - Razali, Ahmad Bazli; Abdullah, Mohd Azizuddin; Wan Ibrahim, Wan Nurulain Nabilah (2020)
The wood-based sector is still one of the major contributors to the Malaysian economy, and it is an important segment of Malaysia’s dynamic manufacturing sector since the emergence of sawmilling and plywood industries. Thus, this study was conducted to determine the variables in relationship marketing, namely communication, commitment, customer satisfaction and trust that has significant effect to company performance at Terengganu state-owned sawmill company Pesaka Trengganu Berhad. The target sample consists of customers of the company that worked in a different department. Data collection was conducted using survey methodology using as the main instrument, which was completed by 73 respondents. The data collected was analysed using SPSS employing descriptive analysis such as frequency and mean analysis, as well as inferential analysis such as Pearson correlation coefficient and multiple regression analysis. Based on the descriptive analysis, respondents in this study perceived at very high level each variable in relationship marketing and company performance. Correlation analysis revealed that all element variables of relationship marketing were found to have a significant positive and moderate level of correlation with company performance, where customer satisfaction showed the highest coefficient (r = 626), followed trust (r = 0.541).and communication (r = 0.511), whereas commitment (r = 0.497) obtained the lowest coefficient value but maintained its significance at p < 0.01. Multiple regression analysis also was conducted in this study with significant relationship for all the variables. In this sense, the company management should strongly focus more on satisfying the customer’s needs and requirements as well as building trust in order to gain favourable perception among its customer into believing that the company is doing their best to cater to their needs and ultimately improve their company performance.